Reproduction of Tolerance Habitus in High School Students in the VUCA Era (Volatility, Uncertainty, Complexity, Ambiguity) (Open Society Conference, 2024)
The progress of Industry 4.0 has had both positive and negative impacts. One of the impacts that can be felt by today's teenagers is a lack of character development. Character cultivation is carried out not only in the family environment, but can also be done in the school environment. School is an arena for cultivating character values ​​for its students. One of the most highlighted character cultivation in the current era is the cultivation of the character of tolerance between religious communities. Departing from these problems, this research aims to discuss the habitus of tolerance in schools in the VUCA Era (Volatility, Uncertainty, Complexity, Ambiguity), especially for students who are Generation Z. The method used in this research is qualitative by in-depth interviews with school students and conducting Focus Group Discussion (FGD) with student representatives at the Surakarta Ex-Karisidenan. The results of this research show that the UCA Era (Volatility, Uncertainty, Complexity, Ambiguity) has an impact on the process of reproducing the habitus of tolerance in schools. This is because digital processes in the VUCA Era (Volatility, Uncertainty, Complexity, Ambiguity) tend to strengthen polarization and increase disagreement between different groups. When information disseminated via social media or other online platforms tends to mislead or oversimplify the complexity of issues, this can result in stigma, stereotypes, and prejudice against certain groups.